2022
DOI: 10.3389/fonc.2022.852515
|View full text |Cite
|
Sign up to set email alerts
|

BAP1-Related ceRNA (NEAT1/miR-10a-5p/SERPINE1) Promotes Proliferation and Migration of Kidney Cancer Cells

Abstract: BackgroundBAP1 is an important tumor suppressor involved in various biological processes and is commonly lost or inactivated in clear-cell renal cell carcinoma (ccRCC). However, the role of the BAP1-deficient tumor competing endogenous RNA (ceRNA) network involved in ccRCC remains unclear. Thus, this study aims to investigate the prognostic BAP1-related ceRNA in ccRCC.MethodsRaw data was obtained from the TCGA and the differentially expressed genes were screened to establish a BAP1-related ceRNA network. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Colony formation was assessed by seeding cells into 6‐well plates (500 cells/well) in triplicate and culturing for 10 days, after which the colonies were fixed, stained, and counted. For the EdU assay kit (RiboBio), cells were seeded into 24‐well plates (3 × 10 4 cells/well) in triplicate, cultured for 24 h, then incubated with 50 μM EdU for 2 h. Subsequent staining and visualization were performed 76 . The EdU assay involves the addition of a penetrant to cell climbing slides that have been prepared and subsequently incubated in a rocker device for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colony formation was assessed by seeding cells into 6‐well plates (500 cells/well) in triplicate and culturing for 10 days, after which the colonies were fixed, stained, and counted. For the EdU assay kit (RiboBio), cells were seeded into 24‐well plates (3 × 10 4 cells/well) in triplicate, cultured for 24 h, then incubated with 50 μM EdU for 2 h. Subsequent staining and visualization were performed 76 . The EdU assay involves the addition of a penetrant to cell climbing slides that have been prepared and subsequently incubated in a rocker device for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…For the EdU assay kit (RiboBio), cells were seeded into 24‐well plates (3 × 10 4 cells/well) in triplicate, cultured for 24 h, then incubated with 50 μM EdU for 2 h. Subsequent staining and visualization were performed. 76 The EdU assay involves the addition of a penetrant to cell climbing slides that have been prepared and subsequently incubated in a rocker device for 10 min. Subsequently, the EdU staining reaction solution was added and incubated at room temperature for 30 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…SERPINE1 is a well-known component of human secretome involved in senescence, fibrosis, and cancerous progression [ 51 53 ], released by cancer cells [ 52 , 54 56 ] and TME components including adipocytes, osteoblasts, CAFs, and MSCs [ 57 61 ]. High SERPINE1 expression correlates with the immune infiltration in ccRCC tumors [ 62 ] and poor prognosis for ccRCC patients [ 63 ]. SERPINE1 acts in an autocrine manner, contributing to the motility of ccRCC cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve (AUC) of the receiver operating characteristic curve analysis indicated that SERPINE1 (AUC=0.789) and miR-10a-5p (AUC=0.892) had good prognostic performance. Furthermore, SERPINE1 expression was positively associated with the levels of immune infiltration of CD4 + T cells, CD8 + T cells, macrophages, dendritic cells and neutrophils ( 82 ). In another study, a ceRNA regulatory network consisting of the lncRNA MMP25-AS1/hsa-miR-10a-5p/SERPINE1 axis was identified.…”
Section: Lncrnas and Cancermentioning
confidence: 99%